2011
DOI: 10.1007/s00410-011-0695-3
|View full text |Cite
|
Sign up to set email alerts
|

The legacy of crystal-plastic deformation in olivine: high-diffusivity pathways during serpentinization

Abstract: Crystal-plastic olivine deformation to produce subgrain boundaries composed of edge dislocations is an inevitable consequence of asthenospheric mantle flow. Although crystal-plastic deformation and serpentinization are spatio-temporally decoupled, we identified compositional readjustments expressed on the micrometric level as a striped Fe-enriched ( " X Fe = 0.24 ± 0.02 (zones); 0.12 ± 0.02 (bulk)) or Fe-depleted ( " X Fe = 0.10 ± 0.01 (zones); 0.13 ± 0.01 (bulk)) zoning in partly serpentinized olivine grains … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
26
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 97 publications
7
26
0
Order By: Relevance
“…The in situ study also shows that olivine reactivity with respect to dissolution can vary from one crystallographic surface to another as well as in different parts of the same surface with similar characteristics, such as terraces. Finally, the observation of precipitate formation on surfaces associated with outcropping defects supports the natural observations of preferential serpentinization along these defects (Plümper et al 2012b) implying that it will be the reactivity of these surfaces that will control olivine reactivity in nature. A recent discussion of the general implications of variable dissolution rates of different crystal surfaces and their evolution with time, to conventional flow-through dissolution experiments on powders can be found in Lüttge et al (2013).…”
Section: Discussionsupporting
confidence: 55%
“…The in situ study also shows that olivine reactivity with respect to dissolution can vary from one crystallographic surface to another as well as in different parts of the same surface with similar characteristics, such as terraces. Finally, the observation of precipitate formation on surfaces associated with outcropping defects supports the natural observations of preferential serpentinization along these defects (Plümper et al 2012b) implying that it will be the reactivity of these surfaces that will control olivine reactivity in nature. A recent discussion of the general implications of variable dissolution rates of different crystal surfaces and their evolution with time, to conventional flow-through dissolution experiments on powders can be found in Lüttge et al (2013).…”
Section: Discussionsupporting
confidence: 55%
“…; Plümper et al. ). We have also examined the rough surfaces of olivine grains that have been freshly broken from the meteorite to obtain a new perspective on the microstructure of the veins and their secondary minerals.…”
Section: Introductionmentioning
confidence: 98%
“…Morales et al (2013) demonstrate the transformation of fabric patterns from olivine to antigorite based on the topotactic relationships. Plümper et al (2012) described an olivine-bearing antigorite serpentinite from the Leka Ophiolite Complex, Norway, and concluded that antigorite serpentinization is initiated along sub-grain boundaries in olivine, supporting the topotactic model.…”
Section: Introductionmentioning
confidence: 89%